Analisis Disiplin Kerja Karyawan Terhadap Kinerja Kantor Desa Panyadap - Nurfajrin, Shofa; Maryono, Dicky (Jurnal Online Manajemen ELPEI, 2025)
This research is motivated by the performance and discipline of the apparatus in Panyadap village which has not achieved optimal results. The purpose of this study is to describe the level of work discipline and performance of the Panyadap village apparatus, as well as to analyze the factors that influence performance in the Panyadap village office. This study uses a qualitative approach with a descriptive type. Data were obtained through interviews involving seven respondents. Data collection techniques used include observation, interviews, and documentation. After the data was collected, the steps taken were classification, examination, processing, analysis, and drawing conclusions. The results of the study indicate that the level of employee discipline in the Panyadap Village Office has not been running optimally. The work discipline in question includes compliance with existing regulations, responsibility in carrying out tasks, and discipline in working hours. However, employee work discipline is still low, as seen from the fact that there are still employees who are not punctual in arriving and leaving, which has an impact on the decline in the performance of the Panyadap Village office. In addition, there are employees who tend to delay the implementation of tasks. Factors that influence employee work discipline include a lack of communication between employees and superiors, as well as low awareness of being punctual and carrying out tasks well.